Pengaruh Era Digital Terhadap Pengembangan Pembelajaran Mandarin - Nike Ardila Ndruru; Rudiansyah Rudiansyah (Jurnal Bahasa, Sastra, dan Budaya, 2022)
The purpose of this research is to know the influence of the digital age on the development of Mandarin learning. This research is descriptive research with a survey method. The subjects in this study were third-year students from the University of North Sumatra majoring in Chinese Literature, totaling 35 respondents. The results of the study found that the availability of various digital media presenting various learning content in Mandarin makes Mandarin more accessible and learned by its enthusiasts. Efficiency is the reason why learning Mandarin through digital media is growing very rapidly. Hence, it can be said that the digital age has greatly influenced the development of Mandarin.Keywords: Digital Age; The Development;  Mandarin Learning